Whispers of the Unspeakable: New York and Montreal Newspaper Coverage of the Oscar Wilde Trials in 1895 - Robinson, Greg (Journal of Transnational American Studies, 2015)
Greg Robinson’s article “Whispers of the Unspeakable: New York and Montreal Newspaper Coverage of the Oscar Wilde Trials in 1895,” originally published in 2010 in the French-language journal Rue des Beaux Arts, no. 24 (2010), is here republished and—with much gratitude—translated (for the original text, please see http://www.oscholars.com/RBA/twenty-four/24.7/Articles.htm). Robinson’s transnational study focuses on how reading the specific language of newspaper reports of the Oscar Wilde case, literally from a distance, from places less emotionally attached to and nationally distinct from the scandal’s epicenter in London, England, provides insight into “the state of everyday public knowledge and discussion of (homo)sexuality, at least west of the Atlantic”; thus Robinson’s fascinating research, which involves numerous newspapers—from the elite New York Times to the New York Herald, from the Montreal Daily Star to the French-language papers of Quebec—concludes that the popular press, read transnationally, offers key insights into the developing attitudes toward and levels of interest in the newly forming identity of the “homosexual” across societies.
En accès libre : https://escholarship.org/uc/item/74n7c590
Keywords: 1800-1899; amériques; analyse comparée; analyse de discours; approches et analyses; cours; discipline; discours dominant; discours médiatique; his4860; histoire; homophobie; hétérosexisme; montréal; new york; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

La différence sexuelle au cabinet des anthropologues parisiens à la fin du XIXe siècle - Rodriguez, Eva (Emulations - Revue de sciences sociales, 2015)
Dans le dernier tiers du XIXe siècle, l’anthropologie biologique, et a fortiori, l’anthropométrie, se consacre en France comme une démarche scientifique que la standardisation des méthodes et des instruments doit garantir. Reposant sur un naturalisme direct, elle se présente comme une entreprise d’objectivation et de hiérarchisation des différences, principalement raciales. Dans cet article, il s’agit d’étudier comment, dans ce corpus anthropologique (notamment dans les travaux de la Société d’Anthropologie de Paris) la différence sexuelle, qui pouvait troubler les classifications raciales, va être redéfinie comme une différence variable selon les races, au risque de saper les fondements naturalistes sur lesquels repose cette différence des sexes.
Number: 15
Keywords: 1800-1899; 1870-1879; 1880-1889; 1890-1899; anthologie; approches et analyses; cours; discipline; discours dominant; europe; france; justice sociale; paris; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail